Characterization of Rockwell hardness indenter Tip using image processing and optical profiler and evaluation of measurement uncertainty. (2nd December 2014) - Moona, G.; Sharma, R.; Sharma, D.; Ojha, V.N.
Abstract : Hardness is a measure of the resistance of a material to be penetrated and eroded by sharp projections of other materials such as diamond. The process of creating sharp projections on any test surface is known as indentation. Hardness measurement of any material is the result of a complex process of deformation during indentation. The indenter tip geometry, which includes radius of curvature at the tip and tip angle, affects the hardness measurement by influencing the nature of the penetration process on the test surface, because every indenter deforms the specimen surface with a different geometry. The controlled indenter geometry can improve the consistency of hardness measurement. In this paper we report the estimation of two important geometrical parameters, radius of curvature and tip angle of a Rockwell indenter by using a simple method of image processing and compare the results with those obtained with a traceable 3D optical profiler. Evaluation of uncertainty in measuremts is carried out as per ISO guidelines (ISO-GUM) and a detailed uncertainty budget is presented. The tip angle estimted is 119.95 degree. The radius of curvature is estimted to be 199.96 ± 0.80 μ m by image analysis which agrees well with the value estimated by using optical profiler i.e. 199.12 μ m.